Testing the climatic controls on plague (Yersinia pestis) using palaeobiogeographical modelling and experimental microbiology - Fell, Henry Gillies (2022)
Yersinia pestis is the bacterial agent of plague, a disease which has caused three trans-continental pandemics through the Common Era. Y. pestis is currently present in reservoir populations in Asia, Africa, North and South America and has recently been identified as a re-emergent disease primarily due to increasing recorded cases across Africa. Plague is a zoonotic disease, the bacterial agent of which (Y. pestis) is transmitted and maintained primarily through rodent reservoir species and the ectoparasites which feed on them. The Y. pestis zoonotic disease system is therefore highly complex as the dynamics of the bacterium, vector and reservoir species can all impact transmission and dissemination.